Muslim converts as a heuristic device for postsecular thinking: agonism as an alternative approach - Olusola, Jeremiah O. A. (Journal of Religious Education, 2023)
The public resurgence of religious adherence in the West remains one of the defining qualities of this century. If secularisation theory can be understood to articulate the inevitable secularisation of post-enlightenment European societies, religious converts may be understood to epitomise some of the theory's failings. Through a narrative-ethnographic investigation into the identity configurations and educational experiences of fifteen millennial (born between 1981 and 1996) Muslim converts, my doctoral research indicates that these converts tend to construct deeply religious identities, characterised by scriptural literalism. Set within the backdrop of an educational context that some perceive as increasingly censorious, these convert Muslims provide a heuristic device with which to examine the contested public spaces in which religious subjectivity can be expressed. This paper will bring literature challenging the securitisation agenda in education, into conversation with theories resistant to the impulse to seek consensus in social and educational debate. Advocating for more agonistic approaches to education, I will present examples from my data that warn of the ways in which "hardened" secular and liberal biases may contribute towards an unmooring of the pluralistic endeavour. Located within contemporary debates about the importance of religion as a discursive aspect of modernity, the chilling of free speech and the place of transgressive thought, the paper encourages an expansion of opportunities to disagree.